The Integrated Local Chicken Farming in Enhancing the Value of Domestic Waste as Empowering BSU ASRI Waste Banks - Lelono, Asmoro; Nur Asyia Alfiyani; Intani, Rini Nur; Nurdian, Yudha; Utami, Eva Tyas; Wijaya, Rizky Surya; Aurellia, Naurah Septa (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2025)
Empowering of the Waste Bank Unit (BSU) through business diversification and optimization of waste utilization has become an urgent need in an effort to increase income and the sustainability of its activities. The Biology Department is collaborating with BSU ASRI, which has been operating since 2021 as a partner and has experience and knowledge in waste management, striving to applicate research results. The Zoological Integrated and Research Application (ZIRA) Research Group, with an interest in native chicken farming research in the field of Avian Immunity, is attempting to implement a model of native chicken farming to utilize organic waste that was previously used as feed for Black Soldier Fly (BSF) maggots. Previously, BSU ASRI utilized organic waste for raising BSF maggots as protein-rich animal feed. The methods used were: incubation of a ready-to-produce chicken farming model by building coops and managing their maintenance, incubation of household-scale farming by providing 1-month-old chicks to BSU members, and independent chick production using a small-scale electric incubator. The results of the activities showed a positive response from the community, as seen from their willingness to raise chickens and the beginning of its adoption in several households. Another benefit is the use of chicken livestock products, starting from ready-to-consume eggs and manure, as well as the utilization of maggot production as part of organic waste utilization.